Glamping as a Tool for Sustainable Tourism Development of Protected Areas: Ukraine's Experience - Yuliia Dashchuk; Liudmyla Matviichuk; Tetiana Zubekhina (Jan Długosz University in Częstochowa, 2024)
The article is devoted to finding solutions to increase the efficiency of using the tourist potential of protected areas in compliance withthe principles of rational nature management, sustainable development and environmental safety. Thus, the authors see the developmentof glamping services as one of the ways to increase the number of tourist flows, attract people to recreation in the natural environment and,at the same time, preserve biodiversity. Ukraine has a significant potential of natural and recreational areas, but the level of its use for tourist purposes is insufficient, and the number of visitors to natural parks and reserves is lower than in similar facilities in foreign countries. The authors present a scheme of territorial organization of key parks and reserves, and systematize the hierarchical structure of subordinating the institution of the Nature Reserve Fund of Ukraine of national importance to various institutional units. The existing experience of usingglamping in the territories of national nature parks in Ukraine for the development of ecological tourism is considered. The analysis of domestic glamping companies is carried out and their competitive advantages are highlighted. The study shows that Ukraine has all the prerequisites for the development of ecological tourism in protected areas with the use of glamping services. The study was conductedbased on the analysis of statistical reports, UNWTO data, and information from Ukrainian government agencies. The methodological toolsof the study include analytical, statistical, comparative geographical, mathematical methods, as well as methods of generalization and systematization.